Nauka czytania partytur dla akompaniatorów - pierwszy etap = Learning to read scores for accompanists - introduction - Czaposki, Michał (Kraków ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
Justification for the need to teach accompanist in reading scores - the need to synchronize performance - the need for thorough knowledge of performed piece - the need for pedagogical and rehersal purposes. Defining in the terms of the score (notes for the band),of the accompanist (musician dealing with the accompaniment), of the accompaniment (harmonic, rhythmic or color complement in the musical composition and musical complement of other activities).
Keywords: akompaniament; akompaniator; klucz altowy; klucz basowy; klucz mezzosopranowy; klucz tenorowy; klucz wiolinowy; nuta kluczowa; partia solowa; partytura; solista; tonacja; transpozycja; znaki chromatyczne przygodne; znaki chromatyczne przykluczowe; accidentals; accompaniment; accompanist; alto clef; bass clef; form of clef; key; key signature; mezzo-soprano clef; score; solo part; soloist; tenor clef; transposition; treble clef